ウミタカマル ニヨル キショウ カンソク - 柳川, 三郎; ヤナガワ, サブロウ; 小竹, 勇; コタケ, イサム; 松生, 洽; マツイケ, カナウ; YANAGAWA, Saburo; KOTAKE, Isamu; MATSUIKE, Kanau (国立極地研究所, 1963)
P(論文) On the cruise in the Antarctic Ocean by the UMITAKA-MARU, the hourly general observation on weather: surface pressure, air temperature, area of clouds, wind force and direction were made from Dec. 3, 1961 to Jan. 30, 1962. The region of observation was divided into three sections and was made the statistics of mean weather condition of these data. In addition, the frequence of wind speed and wind direction were shown every ten days and tabulated separately. departmental bulletin paper